Uncommon Association Between Diabetic Ketoacidosis, Thyrotoxicosis, Cutaneous Abscess and Acute Pericarditis in an Immunocompetent Patient: A Single Case Report and Literature Review - Amelie, Martinot; Magalie, Demar; Liliane, Thelusme; Merzaka, Bounoua; Florin, Santa; Maryvonne, Dueymes; Jelena, Vujica; Henry, Dequidt; Nadia, Sabbah (Current Diabetes Reviews, 2020)
Introduction: The typical factors precipitating diabetic ketoacidosis (DKA) include infections (30%), cessation of antidiabetic medication (20%), and a new diagnosis of diabetes (25%). The etiology remains unknown in 25% of cases. Less frequent causes cited in the literature include severe thyrotoxicosis and, infrequently, pericarditis. Few publications have described the role of human T lymphotropic virus type 1 (HTLV-1) in endocrine and metabolic disorders. Based on a clinical case associated with several endocrine and metabolic disorders, we suggest a potential role for HTLV-1, an endemic virus in the Amazonian area, and review the literature concerning the role of this virus in thyroiditis, pericarditis and diabetes mellitus. Case Report: A fifty-year-old Surinamese woman without any medical history was admitted for diabetic ketoacidosis. No specific anti-pancreatic autoimmunity was observed, and the C-peptide level was low, indicating atypical type-1 diabetes mellitus. DKA was associated with thyrotoxicosis in the context of thyroiditis and complicated by nonbacterial pericarditis and a Staphylococcus aureus subcutaneous abscess. The patient was infected with HTLV-1. Conclusion: To our knowledge, this uncommon association is described for the first time. Few studies have analyzed the implications of HTLV-1 infection in thyroiditis and diabetes mellitus. We did not find any reports describing the association of pericarditis with HTLV-1 infection. Additional studies are necessary to understand the role of HTLV-1 in endocrine and cardiac disorders.
Keywords: Diabetes mellitus